Evaluasi Kebijakan Sekolah Ramah Anak di SD Negeri Kandangan, Kecamatan Krembung, Kabupaten Sidoarjo - Tri Eka Cahyana; Aris Sunarya; Sri Kamariyah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The Child Friendly School policy is an important instrument in protecting children's rights and preventing violence in educational environments. This research aims to evaluate the implementation of the Child Friendly School policy at SD Negeri Kandangan, Krembung District, Sidoarjo Regency using William Dunn's policy evaluation approach. This research uses qualitative methods with a descriptive approach. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation studies. Research informants were selected using purposive sampling techniques consisting of school principals, teachers, school committees, and students. Data analysis techniques use the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The research results show that the evaluation of policy effectiveness achieves a fairly good level of success in creating a safe and comfortable learning environment, although there are still some teachers who use conventional disciplinary methods. The efficiency evaluation shows that schools optimize limited resources through community participation and village government support. The adequacy evaluation identifies the need for improved facilities such as prayer rooms and special rooms for students with special needs. The equity evaluation shows the school's commitment to providing inclusive educational services without discrimination. The responsiveness evaluation shows high stakeholder satisfaction with child-friendly school programs. The accuracy evaluation confirms that this policy is appropriate for inclusive schools that have students with special needs. This research contributes to the development of educational policy evaluation with a focus on child protection in inclusive schools.